2015
DOI: 10.1177/0886260515614562
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in the First 2 Years of Life: Implications for Toddlers’ Behavior Regulation

Abstract: Intimate partner violence (IPV) is prevalent in families with young children and challenges their healthy development. This study examined characteristics of IPV (e.g., mother- vs. partner-perpetrated, types and severity) and investigated potential effects of IPV on toddlers' behavioral regulation in a sample of families at risk for IPV. We also examined whether maternal depression and child-rearing attitudes and behavior would moderate IPV-child behavior links. These questions were addressed in a sample ( N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
5
24
0
3
Order By: Relevance
“…In a recent study by Zarling et al (2013), maternal harsh parenting mediated the association between exposure to IPV and externalizing problems in a community sample of low socioeconomic status families aged 6–8 years ( N = 132). These findings were consistent with those of Easterbrooks, Katz, Kotake, Stelmach, and Chaudhuri (2015) in a larger, at-risk sample of mothers and their children aged 1–2 years ( N = 400). Children who had witnessed IPV and experienced harsh parenting, specifically corporal punishment, had more severe behavior problems.…”
Section: Maternal Factors and Child Externalizing Problems In The Consupporting
confidence: 87%
See 1 more Smart Citation
“…In a recent study by Zarling et al (2013), maternal harsh parenting mediated the association between exposure to IPV and externalizing problems in a community sample of low socioeconomic status families aged 6–8 years ( N = 132). These findings were consistent with those of Easterbrooks, Katz, Kotake, Stelmach, and Chaudhuri (2015) in a larger, at-risk sample of mothers and their children aged 1–2 years ( N = 400). Children who had witnessed IPV and experienced harsh parenting, specifically corporal punishment, had more severe behavior problems.…”
Section: Maternal Factors and Child Externalizing Problems In The Consupporting
confidence: 87%
“…Further corroborating evidence comes from a number of other studies (Clarke et al, 2007; Fredland, Campbell, & Han, 2009; Holmes, 2013; Lieberman, van Horn, & Ippen, 2005; Maddoux et al, 2016). On the other hand, other studies have found that maternal psychopathology including depression did not mediate the relationship between IPV and child disruptive behaviors (Easterbrooks, Katz, Kotake, Stelmach, & Chaudhuri, 2015; Ehrensaft & Cohen, 2012; Graham-Bermann, Howell, Lilly, & DeVoe, 2011).…”
Section: Maternal Factors and Child Externalizing Problems In The Conmentioning
confidence: 68%
“…Another study explored the effects of exposure to partner violence on women and their children and found that maternal mental health functioning was directly related to child psychopathology on the Child Behavior Checklist (Maddoux et al, 2016). Results of a recent study showed that the severity of maternal psychopathology among mothers who reported experiencing IPV was associated with greater behavioral problems among toddlers (Easterbrooks, Katz, Kotake, Stelmach, & Chaudhuri, 2015).…”
Section: The Link Between Maternal Ptsd and Child Psychopathologymentioning
confidence: 99%
“…Although relatively fewer longitudinal studies have been conducted in this area (Evans et al, 2008), early evidence supports the association between IPV and child behavior problems over time, with IPV exposure more strongly linked to externalizing problems for younger children and internalizing problems for older children (Vu et al, 2016). First-time mothers' reports of physical and psychological IPV, either as victim or as perpetrator, were each associated with their reports of their toddlers' higher behavior problems a year later (Easterbrooks et al, 2018). Toddlers who experienced corporal punishment or PCA were rated as having higher child behavior problems in the presence of mothers' psychological IPV (either victimization or perpetration), relative to children who had not (Easterbrooks et al, 2018).…”
Section: Longitudinal Studiesmentioning
confidence: 99%